2017
DOI: 10.3389/fmars.2017.00410
|View full text |Cite
|
Sign up to set email alerts
|

Abyssal Solenogastres (Mollusca, Aplacophora) from the Northwest Pacific: Scratching the Surface of Deep-Sea Diversity Using Integrative Taxonomy

Abstract: Solenogastres (Aplacophora) is a small clade of marine, shell-less worm-molluscs with close to 300 valid species. Their distribution ranges across all oceans, and whereas the vast majority of species has been collected and described from the continental shelf and slope, only few species are known from depths below 4,000 m. Following traditional taxonomy, identification of specimens to species level is complex and time-consuming and requires detailed investigations of morphology and anatomy-often resulting in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Originating in the 1970s, interactive keys using Descriptive Language for Taxonomy (DELTA) methodologies as an instrument for identifying species are not new (Dallwitz, 1974), but their use in deep-sea taxonomy has thus far been rudimentary (Saucède et al, 2021). Overall, there is a paucity of any type (paper or digital) of identification key and guide in general 3 and for deep-sea taxa in particular (Miljutin et al, 2010;Gollner et al, 2014;Bergmeier et al, 2017); instead, identifications are mostly based on descriptive works that are distributed throughout the literature (cf. Glover et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Originating in the 1970s, interactive keys using Descriptive Language for Taxonomy (DELTA) methodologies as an instrument for identifying species are not new (Dallwitz, 1974), but their use in deep-sea taxonomy has thus far been rudimentary (Saucède et al, 2021). Overall, there is a paucity of any type (paper or digital) of identification key and guide in general 3 and for deep-sea taxa in particular (Miljutin et al, 2010;Gollner et al, 2014;Bergmeier et al, 2017); instead, identifications are mostly based on descriptive works that are distributed throughout the literature (cf. Glover et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this recent expedition series to the spanning a depth range from 3,000 to more than 9,500 m (see Bergmeier et al 2017Bergmeier et al , 2020Ostermair et al 2018).…”
Section: Richness Patternsmentioning
confidence: 99%
“…Therefore, for a first classification into morphospecies, the general external appearance is important, and several authors have highlighted the usefulness of this and the sclerites to discern between lineages (Scheltema et al . 2012; Kocot and Todt 2014; Bergmeier et al . 2017; Cobo and Kocot 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of the study of the scleritome and DNA barcodes has been shown to allow a tentative identification of specimens, albeit at the family level in some cases, without the need for time-consuming or expensive techniques, improving the ability to estimate the number of lineages in a collection (e.g. Bergmeier et al . 2017, 2019).…”
Section: Introductionmentioning
confidence: 99%